WRITING A RECOUNT TEXT: AN ANALYSIS OF THE EIGHTH - GRADE STUDENTS' DIFFICULTIES AT MTS PIDUA - Kiki Rizki Amelia; Rekha Asmara; Dewi Sartika (Universitas Islam Ogan Komering Ilir Kayuagung, 2023)
Writing is a challenging skill that students must master. Students must understand aspects of writing, including content, organization, grammar, vocabulary, and mechanics to compose well. The objective of this study was to investigate eighth-grade students’ difficulties in writing recount text at VIII MTs Pidua. A qualitative study was applied. The samples were the eighth-grade students of MTs Pidua consisting of 14 students. To collect the data, a written test in the form of an essay and a questionnaire consisting of eight questions related to grammatical, knowledge and understanding, practice, and educational background were employed. Two raters scored the students’ writing products using an analytic scoring rubric. To validate the data, the triangulation method was applied. To analyze the data, Miles and Heberman’s three steps were used: data reduction, data display, and conclusion drawing or verification. The findings revealed that the number of learners made it challenging to write a recount text. These difficulties were linked to writings aspects such as content (35.71%), vocabulary (35.71%), grammar (21.43%), and organization (21.43%). The students, on the other hand, were well-versed in mechanics. They understood the importance of punctuation, spelling, and capitalization when writing a recount text. However, the students had difficulty in writing a recount text due to limitation knowledge of grammar, less understanding of the recount text, and less practice at writing. In conclusion, the eighth-grade students at MTs Pidua still struggled with essential elements of writing that should be considered while creating a recount text